Empowering Community Health Cadres through Integrated Health Education to Improve Early Detection and Management of Chronic Diseases: A Community-Based Participatory Approach - Priyo Sasmito; Normayanti Rambe; Tiasa Pohan; Ageng Septa Rini; Siti Khadijah Batubara; Zainuddin Zainuddin; Martua Siregar; Dolly Putra Parlindungan; Burhanuddin Burhanuddin (International Journal of Community Service (IJCS), 2026)
Chronic diseases, such as hypertension and diabetes mellitus, present a significant and growing public health burden in many developing regions, including rural Indonesia. Community Health Cadres (CHCs) are pivotal frontline health volunteers, yet they often lack the comprehensive knowledge and practical skills necessary for effective early detection and community-based management of these conditions. This community service program aimed to empower CHCs through an integrated health education intervention, employing a community-based participatory approach. The program was implemented in [Sebutkan Lokasi, misal: five villages in Yogyakarta] over a six-month period and involved 45 CHCs. The intervention comprised a series of structured training workshops, hands-on practice sessions using portable health devices (e.g., digital sphygmomanometers and glucometers), and the development of simple patient-record-keeping tools. The participatory approach ensured that the CHCs were actively involved in identifying local challenges and co-designing feasible solutions. Pre- and post-intervention assessments revealed a statistically significant improvement in the CHCs' knowledge scores (p < 0.001) and their practical competency in conducting basic health screenings. Furthermore, there was a notable increase in the number of community members referred to primary health centers for confirmatory diagnosis. This program demonstrates that empowering CHCs through targeted, integrated education, grounded in participatory principles, is a viable and effective strategy to strengthen primary healthcare systems. It enhances the capacity for early disease detection and promotes sustainable chronic disease management at the grassroots level, underscoring the critical synergy between community education and public health outcomes.